Characterization of the role of endogenous cholecystokinin on the activity of the paraventricular nucleus of the hypothalamus in rats - Cano, Victoria (2003)
1. Activation of the hypothalamic–pituitary–adrenal axis by fasting seems to involve cholecystokinin (CCK) receptors. 2. This work aims to characterize the role of endogenous CCK in the activity of the paraventricular nucleus (PVN) of the hypothalamus during food withdrawal. We investigated, by c-Fos immunohistochemistry, the effect of CCK(1) and CCK(2) receptor antagonists (SR-27,897 and L-365,260, respectively) on c-Fos levels expression induced by food deprivation. 3. Under our conditions, the number of cells expressing c-Fos was reduced both by SR-27,897 and L-365,260 in food-deprived rats. 4. To investigate the importance of glucose availability, we studied the effect of CCK receptor antagonists on c-Fos synthesis induced by the glucose antimetabolite 2-deoxyglucose. In these animals, only SR-27,897 decreased c-Fos expression in the PVN. 5. Our results indicate that the effect of CCK antagonists is mainly perceptible when glucose availability decreases, and suggest that CCK-ergic inputs could drive the activity of the PVN under fasting/low glucose conditions.